Catalytic hydrothermal liquefaction of algae and upgrading of biocrude: A critical review. (December 2018) - Xu, Donghai; Lin, Guike; Guo, Shuwei; Wang, Shuzhong; Guo, Yang; Jing, Zefeng
Abstract: Over the last two decades, the hydrothermal liquefaction (HTL) of algae has emerged as a promising technology for producing liquid bio-oil to meet increasing energy demands and reduce environmental pollution. In this article, the present research status of the catalytic HTL of algae and the catalytic hydrothermal upgrading of biocrude (crude bio-oil) is systematically reviewed and analyzed. The corresponding catalytic characteristics (such as the catalytic effect on the biocrude yield and quality and the related influencing factors) and catalytic mechanisms (e.g., hydrogenation, deoxygenation, decarboxylation, denitrogenation and desulfurization) during algae HTL as well as the approaches for upgrading of biocrude are summarized and analyzed comprehensively. Another potential technological flow for bio-oil production from algae HTL is proposed, and a comparison between direct catalytic HTL and the two-step production method is presented for the first time. Moreover, contemporary problems and subsequent research directions are presented. Highlights: Analyze catalytic performances of various catalysts on algae HTL and biocrude upgrading. Summarize catalytic reaction mechanisms of hydrogenation and heteroatom removal. Compare the characteristics of direct catalytic HTL and the two-step producing method. Propose a potential whole technological flow concerning bio-oil production from algae HTL. Recommend some future research directions on catalytic algae HTL and biocrude upgrading.